The Miracle of Arabic Language: From Pre-Islamic To Islamization - Muhammad Kurnia; Rahmat Hidayat (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2022)
Language contributes greatly to human civilization. Among the world's major languages ​​spoken by mankind is Arabic. Arabic influences many aspects of life, such as Roman civilization in many fields, even music and poetry. Jahiliyyah Arabic only serves as a literary language. But when Islam came, Arabic underwent a very significant development, becoming the language of science. This is what is meant by the process of Islamization. This study aims to explain the influence of Islam on Arabic. Therefore, through this paper it can be concluded that even though there are several Arabic terms that are the same as those used during the Jahiliyyah and the advent of Islam, basically they have different meanings and emphasis. Islam came to have an influence in facilitating the pronunciation of Arabic terms which were previously complicated or even providing new Arabic vocabulary that was not known during the Jahiliyya period.